Implied constitutional principles - Zhou, H (2012)
This thesis challenges some of the current limits to the grounds for judicial review of legislation accepted by most Canadian jurists. More specifically, it makes a common law-based argument in favour of the priority over legislation of principles which are implied from the Imperial Constitution Acts 1867-1982 and which originally derive from the English constitution – namely implied constitutional principles. The argument faces two main interrelated legal objections: Parliamentary sovereignty and the Framers’ intentions. The first objection is rebutted by arguing that Parliamentary sovereignty possesses an ability to change in a way that can incorporate substantive legal limitations. The most prevalent common law-based theories of change to Parliamentary sovereignty suggest that the courts can authoritatively determine if implied constitutional principles can check legislation. The second objection is rebutted by reference to the notion of progressive interpretation as conceived under Hartian and Dworkinian theories of law and adjudication. Under these theories, progressive interpretation is an aspect of the courts’ best overall interpretation of the constitution, which includes implied constitutional principles. Such progressive interpretation can result in these principles constraining legislative authority. Justification of the progressive interpretation of implied constitutional principles can be based on the rule of law from which derive a number of these principles. One plausible conception of the Canadian rule of law is that it rejects the view that implied constitutional principles can prevail when in conflict with legislation. However, the better conception is that, as an attempt to adapt implied constitutional principles to relevant changes in society and to protect their underlying values, the judiciary should interpret these principles as capable of checking legislation to the extent that they form part of the core content of the rule of law. Such a conception and an operation of implied constitutional principles can properly be explained by Hartian or Dworkinian common law-based progressive interpretation of these principles and by their relationship with legislative authority.